Managerial Strategy Facing the Challenges of Globalisation and the Digital Era - Afriantoni (Al-Hayat: Journal of Islamic Education, 2024)
This study aims to analyse the various challenges faced by Islamic Religious Education (PAI) teachers at Junior High School (SMPN) 3 Palembang in the era of globalisation and to identify managerial innovations that can be applied to improve the quality of Islamic religious education. This study uses a qualitative approach with a case study type at SMP Negeri 3 Palembang. Data was collected by interviewing teachers and principals, observing how schools implement managerial strategies, and documenting the Lesson Plan, training reports, policies, and student learning outcome data. Data validity testing with triangulation of sources and methods. Qualitative data analysis using Miles and Huberman. The results of the study show that the challenges faced by SMP Negeri 3 Palembang include challenges in the use of technology, challenges in teacher competence, and challenges in diversity. Managerial strategies begin with planning with technology training, developing teacher intrapersonal skills, and developing a progressive curriculum. Organisation with collaboration between the treasurer, school committee, and parents of students for technology development, curriculum deputy for development of teacher intrapersonal competence, and curriculum team with Islamic Religious Education teachers for integration of multicultural values. Implementing technology integration in learning, training for teacher competency development, and integrating multicultural values in learning. Control with evaluation of the effectiveness of the use of learning media, evaluation of the application of learning models for teacher competency and evaluation of multicultural values in teaching. Further research is recommended to explore the long-term impact of technology training and multicultural values on student development and evaluate the effectiveness of new teaching methods in the context of cultural diversity in other schools.